Trabeculectomy for congenital glaucoma in University College Hospital, Ibadan: a 7 year review of cases (2015)
Introduction: Congenital glaucoma is an uncommon ocular condition affecting about 1/15,000 live births. About two third of cases are bilateral with a higher prevalence in males. The definitive treatment requires surgery which could be trabeculectomy, trabeculotomy, goniotomy, drainage tubes or a combination of trabeculotomy and trabeculectomy. Aim: To determine the outcome of trabeculectomy in patients with congenital glaucoma seen at the University College Hospital Ibadan between 2007 and 2013. Methods: The medical records of all patients with congenital glaucoma seen between the years 2007 and 2013 were retrieved. Inclusion criteria were patients who had trabeculectomy with or without anti-metabolites within this period. The main outcome measures assessed were postoperative intraocular pressure (IOP) and corneal clarity. Data was analyzed with the statistical Package for Social Sciences version 21. Results: Thirty-four eyes of 18 patients were reviewed out of which 16 patients had bilateral trabeculectomy while two had unilateral trabeculectomy. The mean preoperative IOP was 26.31 mmHg while the mean IOP in the immediate postoperative period, at 3 months after surgery and at last follow-up visit were 13.31 mmHg, 12.78 mmHg and 15.89 mmHg respectively. IOP was <21 mmHg in 81.82% of the eyes as at last clinic visit. All eyes had cloudy corneas preoperatively while 38.24% had minimal residual corneal opacity (Haab’s striae) as at last follow-up visit. Conclusion: In the absence of equipment for other surgical options, trabeculectomy is an effective surgical approach in the management of congenital glaucoma in the short term.